CARES planning survey report, 2012 - Trechter, David; Janke, James; Mather, Becky (My University, 2013)
This survey was developed to gather participants' need for/interest in resources to help parents understand and guide their children through their developmental stages from birth to 18 years of age. The survey also gathered information on challenges facing families as they raise their children and parents' preferred means of accessing information about their children's development.
ii + 38 p.
Keywords: Child development--Wisconsin--Saint Croix County; Child development--Wisconsin--Pierce County; Child rearing--Wisconsin--Saint Croix County; Child rearing--Wisconsin--Pierce County; Parent and child--Wisconsin--Saint Croix County; Parent and child--Wisconsin--Pierce County; Parenting--Wisconsin--Saint Croix County; Parenting--Wisconsin--Pierce County